Citra Islam Moderat: Aksi Cyber PR dari PWNU Jawa Timur - Sam Abede Pareno; M Rif’an Arif (JIKE: Jurnal Ilmu Komunikasi Efek, 2018)
ABSTRACT Religious traditions in Indonesia are known to be very moderate and tolerant abroad is a reflection of the character of a great noble nation. Between religion, tradition and culture are able to perform compounds so as to create a genuine religious harmony. Because of this reality Indonesia is regarded as the largest Muslim majority country in the world that almost without conflict, in the midst of reality Muslim countries in the Middle East that impressed the dispute into the daily menu. However, the reality of Indonesia as a moderate nation is injured by the act of a group that is fond of terrorism and radicalism by riding Islamic religious teachings. Thus, this reversed religion is assumed as a source of cruelty. It is through that phenomenon researcher, feel the need to examine the strategy of disseminating moderate Islam by Nahdlatul Ulama. The selection of this Islamic organization according to the authors due to its success in moderating Islam in Indonesia. In this study, the study using a qualitative approach or method as well as adopting the theory of Van Dijk discourse analysis as a scalpel to peel the discourse of moderate Islam published by PWNU East Java through the website. As for this research, the findings are important, among others are: 1) moderate Islamic discourse campaigned by Nahdlatul Ulama East Java is categorized into three segments, namely social, religious and nationality. 2) the text structure that builds moderate Islamic discourse NU East Java in Van Dijk perspective constructed in three domains, namely text, social cognition and social context. 3) the principles of Public Relationship implemented by NU through cyber (online media), among others; News publications and expert opinions, production of image and video-based information, and updating official NU information to the public about their attitudes and views on the phenomena that occur by promoting the values of Islamic moderatism. Key Word : Islamic Moderatism, Nahdlatul Ulama, Cyber Public Relationship